Procurement Tender Fairness: MSME, Business Competition Law, and SIKaP Application - Asmah Asmah (CV. Media Digital Publikasi Indonesia, 2024)
This study analyzes the right to justice in tenders for the procurement of goods and services for small business actors from the perspective of business competition law through the application of the SIKaP application. The research method used is qualitative analysis based on the available empirical analysis of the literature. The results of the literature analysis show that small business actors face challenges such as the non-transparency of the selection process, unfairness in evaluating proposals, non-neutral procurement, unfair competition, and constraints on access to information. SIKaP application is considered as a potential solution to increase fairness in procurement tenders, but challenges such as lack of understanding and awareness as well as technical obstacles still need to be overcome. The importance of the role of business competition law is also recognized in protecting the rights of small business actors. This study concludes that additional efforts are needed, including training and awareness, technological infrastructure improvements, and effective law enforcement, to ensure the successful implementation of the SIKaP application and the protection of small business actors' rights in procurement tenders. The results of this study make an important contribution in understanding the challenges and opportunities for small business actors in obtaining fairness in procurement tenders. The implications can be used as a basis for developing policies and actions that support fair participation and equal opportunities for small business actors.